2023
DOI: 10.23947/2334-8496-2023-11-2-331-341
|View full text |Cite
|
Sign up to set email alerts
|

Competences of Physical Education Teachers in Education Supported by Digital Technology

Jelena Maksimović,
Natalija N. Lazić

Abstract: The application of digital technology in teaching physical education provides a basis for its improvement in the direction of promoting physical activity and student development. As one of the most important subjects of the teaching process, teachers have a fundamental role in achieving the goals and tasks of physical education. Physical education teachers are required to develop competences based on which they would implement digital technology in physical education classes in compliance with the imperatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Hsua et al [41] found that the characteristics of being useful, compatible, and observable are the most important factors in innovation adoption. In their theoretical analysis, Maksimovic and Lazic [42] pointed out the need for expanding and developing the digital competencies of physical education teachers. Therefore, it is important to make technology useful, understandable, and easily accessible for PE teachers to adopt and use its innovations.…”
Section: Discussionmentioning
confidence: 99%
“…Hsua et al [41] found that the characteristics of being useful, compatible, and observable are the most important factors in innovation adoption. In their theoretical analysis, Maksimovic and Lazic [42] pointed out the need for expanding and developing the digital competencies of physical education teachers. Therefore, it is important to make technology useful, understandable, and easily accessible for PE teachers to adopt and use its innovations.…”
Section: Discussionmentioning
confidence: 99%
“…Technology-supported learning processes contribute to educational excellence (Maksimović & Lazić, 2023). Students can experience various conveniences (Kilag et al, 2023), starting from easy access to the material they need to find learning references (Lee et al, 2023;Petrova & Петрова, 2023).…”
Section: Introductionmentioning
confidence: 99%